Critical Discourse Analysis for Policy Documents: A Case Study of the Adult ESOL Strategy, a New Zealand Government Language and Education Policy - Adesina, Oladapo Olukayode (Auckland University of Technology, 2023)
The study’s theoretical framework is underpinned by Critical Theory, Critical Discourse Analysis (CDA), including Foucauldian Discourse Analysis (FCDA), and Foucault’s concept of Genealogy. Foucaultian critical discourse analysis asks questions about how we as subjects or citizens have been constructed historically; how we have come to define these concepts and have come to think, speak and act in certain ways with regard to them; and the various relations and techniques of +++power by which people come to know themselves as subjects of government policy discourses, and which produce and maintain these as notions that can be thought and acted on (Fadyl et al., 2013). Using Critical Discourse Analysis (CDA) (including Foucault’s work) as a methodological and theoretical guide, the inquiry focuses partly on what the underlying views of The Adult ESOL Strategy text may be in New Zealand and what its discourses and implications are. The Adult ESOL Strategy is seen as part of a ‘governmental assemblage’, in which significant documents play both an executive and educational role, particularly seen in the way they tend to form particular ‘subjectivities’, in accordance with the political philosophy that underpins them. Chapter 1, the Introduction provides an overview as well as a background to the study . The chapter starts with a review of the history and contexts of migrants and adult ESOL in New Zealand, going on to further explain the significance of the study. Chapter 2, the literature review, defines and examines adult ESOL as an academic and policy field and also provides an overview of relevant studies. Chapter 3 gives the background to the Foucauldian Socio-historical analysis as methodology for analysis and mainly discusses the methodology adopted in the study. It outlines approaches to education policy studies, states the principles of CDA and explains its key research tools. In addition, this chapter presents a review of previous studies that have used CDA as a method in educational policy research. It further includes the explanation of the framework for analysis, procedure and the data that the thesis uses. Chapter 4 discusses techniques for analysis. It discusses how Foucault can be used to analyse policy documents. Chapter 5 covers Analytic Method and demonstrates the use of Critical Discourse Analysis to analyse policy documents in a case study of The Adult ESOL Strategy (2003) .This chapter which is mainly an analytical case study of The Adult ESOL Strategy (2003), includes an examination of the construction of the ideal adult ESOL learner in The Adult ESOL Strategy as well as a closer look at, and analysis of , the document in terms of the discourses present in it and the assumptions it holds about the ideal/desired adult ESOL learner. This chapter more transparently provides omnibus economical answers to the two research questions in this study which are (1) What discourses/assumptions does the Adult ESOL Strategy have in relation to adult ESOL learners and immigrants? and (2) What attitude does the Adult ESOL Strategy instantiate in relation to the ‘desirable/quality’ adult ESOL learner? The answers to these research questions are evident in combination: a major theme in the Adult ESOL Strategy is the discourse of the construction of the adult ESOL Learner as an autonomous rational chooser who is a homo-economicus in an atmosphere of neo-liberalism. The particular identity constructed for the adult ESOL learner emphasises independence, co-operation and pro-activity in the quest to be an ideal ESOL learner. The final chapter sums up the study, discusses policy implications and makes recommendations as well as concluding remarks.